2016
DOI: 10.1080/13102818.2015.1114428
|View full text |Cite
|
Sign up to set email alerts
|

TMO: time and memory optimized algorithm applicable for more accurate alignment of trinucleotide repeat disorders associated genes

Abstract: In this study, time and memory optimized (TMO) algorithm is presented. Compared with SmithÀWaterman's algorithm, TMO is applicable for a more accurate detection of continuous insertion/deletions (indels) in genes' fragments, associated with disorders caused by overrepetition of a certain codon. The improvement comes from the tendency to pinpoint indels in the least preserved nucleotide pairs. All nucleotide pairs that occur less frequently are classified as less preserved and they are considered as mutated cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The evolutionary information feature. The evolutionary information has been proved effective in RNAinteracting protein residues prediction and other bioinformatics problems [35]. PSSM is a common representation for evolutionary information and Kumar et al [23] have shown its effectiveness to improve the prediction performance.…”
Section: Feature Representationmentioning
confidence: 99%
“…The evolutionary information feature. The evolutionary information has been proved effective in RNAinteracting protein residues prediction and other bioinformatics problems [35]. PSSM is a common representation for evolutionary information and Kumar et al [23] have shown its effectiveness to improve the prediction performance.…”
Section: Feature Representationmentioning
confidence: 99%